Tinjauan Ketepatan Kode Diagnosis Pada Kasus Bedah Pasien Rawat Inap di RSKD Duren Sawit - Ririn Rahayu; Laela Indawati; Lily Widjaja; Nanda Aula Rumana (Publikasi Indonesia, 2022)
Based on Kenmenkes RI in 2014, it explains about coding which has the meaning as an activity of providing main diagnosis codes and secondary diagnoses in accordance with ICD-10 and providing procedure codes in accordance with ICD-9CM. Coding inaccuracies can affect the financing of health services, this study was conducted to see the accuracy of the main and secondary diagnosis codes of surgical cases of inpatients at Duren Sawit Hospital using descriptive research methods with a quantitative approach, namely writing aims to describe the results obtained on the accuracy of diagnosis codification. Informants in this study were inpatient coders at RSKD Duren Sawit, data collection in this study using interviews and observation methods. The results of this study indicate that the coding SPO uses the latest procedures based on an electronic system, the educational background of the coder at RSKD Duren Sawit has an important role in the quality of the correct code. The competence of the coder at RSKD Duren Sawit still has to undergo deeper learning, in the results of coding research on surgical cases of inpatients, it was found that the average dignosis code that had accuracy was 58 (63.74%) and 33 (36.26%) were inappropriate, and it was also found that the results of the accuracy of the secondary diagnosis were 84 (92.30%) and 7 (7.70%) were inappropriate. Based on the 4 characters, the inaccuracy occurred in the main diagnosis of the majority in the 4th character as many as 31 (34.7%). There are factors that become obstacles to the identification of 5M, namely the man factor, the lack of accuracy of doctors in inputting diagnoses and the lack of accuracy of officers in re-examining incorrect diagnosis codes and having to undergo learning related to coding more deeply for diagnosis coding officers who are not from academic graduates of medical records.